Geospatial assessment of elevated agrivoltaics on arable land in Europe to highlight the implications on design, land use and economic level - Brecht Willockx; Cas Lavaert; Jan Cappelle (Energy Reports, 2022)
Agrivoltaic systems (a combination of agricultural crop production and photovoltaics (PV) on the same land) have an increasing interest. Realizing this upcoming technology raises still many challenges at design, policy and economic level. This study addresses a geospatial methodology to quantify the important design and policy questions across Europe. An elevated agrivoltaic system on arable land is evaluated: three crop light requirements (shade-loving, shade-tolerant and shade-intolerant) are simulated at a spatial resolution of 25 km across the European Union (EU). As a result, this study gives insight into the needed optimal ground coverage ratio (GCR) of the agrivoltaic system for a specific place. Additionally, estimations of the energy production, levelized cost of energy (LCOE) and land equivalent ratio (LER) are performed in comparison with a separated system. The results of the study show that the location-dependent solar insolation and crop shade tolerance have a major influence on the financial competitiveness and usefulness of these systems, where a proper European policy system and implementation strategy is required. Finally, a technical study shows an increase in PV power of 1290 GWp (almost × 10 of the current EU’s PV capacity) if potato cultivation alone (1% of the total arable agricultural area) is converted into agrivoltaic systems.